Teknik Relaksasi Napas Dalam Kombinasi Guided Imagery Berbasis Teori Comfort terhadap Intensitas Nyeri Pasca Bedah Sectio Caesarea - Tanti Dwi Cahyani; Nursalam Nursalam; Wikan Purwihantoro Sudarmaji; Diah Priyantini (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the effect of combining deep breathing relaxation techniques with guided imagery on the pain intensity of postoperative Sectio Caesarea (SC) patients. The method used was a quasi-experiment on women who underwent SC surgery. The results showed a significant effect after the intervention on pain intensity (p=0.000; d=2.876), accompanied by a significant change in pain intensity (p=0.000). In conclusion, breathing relaxation techniques in combination with guided imagery based on the comfort theory can reduce the pain intensity of post-SC surgery patients. Keywords: Comfort Theory, Guided Imagery, Deep Breathing, Pain